Numerical investigations of pipe flow downstream a flow conditioner with bundle of tubes - Guang Yin; Muk Chen Ong; Puyang Zhang (Engineering Applications of Computational Fluid Mechanics, 2023)
Flow conditioners are widely utilized in pipeline systems to improve the precision of flow rate measurement in the pipeline systems of the offshore and subsea oil and gas industry. There is a lack of knowledge about the influences of the conditioners on the flow inside a bend pipe due to the measurement inaccuracy caused by geometries complexity. In this study, numerical simulations are carried out solving the three-dimensional Reynolds-averaged Navier-Stokes (RANS) equations with the κ–ω SST model to investigate the large-scale flow characteristics inside a double bend pipe and the performance of a conditioner with a bundle of 19 tubes. The obtained axial velocity inside a double bend pipe flow with no flow conditioner are compared with those of the previously published numerical simulations results and experimental data as the validation study. Helical flow structures are found behind the double bend and effectively removed by the flow conditioner. The performance of the flow conditioner is evaluated based on the axial flow velocity profiles, the swirl intensities and the deviation from the flow inside a straight pipe. The effects of Reynolds numbers and the lengths of the tube bundle on the flow downstream the flow conditioner are discussed.